DENOISING OF IMAGE USING BILATERAL FILTERING IN MULTIRESOLUTION - Abid Ali, Alaa Abid Muslam; Dohan, Mohammed Iqbal; Musluh, Saif Khalid (APTIKOM Journal on Computer Science and Information Technologies, 2018)
One of the very efficient and resource conservative image processing methodology is with the help of bilateralfilters. This technique filters the image without the help of edge smoothing but it does employs spatial averaging in anon-linear way. The filtering technique discussed above is very much dependent on the parameters of its filters. A veryslight change in filter parameter values effects the outputs and results in a most drastic manner. In this paper, theauthor has worked on two contributions. In the applications concerning image denoising, the author has contributedin study of the parameter selection of bilateral filters which are optimal in nature. The contribution number two isabout extending the present work i.e. extension of the filters which are bilateral in nature. In this process, the bilateralfiltering of images is applied to the lower frequency sub-bands which is also known as approximation sub-band. Thissub-band is obtained by using the wavelet transformations. Hence, a new framework for image denoising will becreated which will be combination of multiresolution bilateral filtering and wavelets transformation techniques. As amatter of fact, this combination is efficient in contradicting noise from an image.